Ideas of a Siberian City: Urban Experiments and Inhabitants’ Feeling - Klevakin, Alexander (project baikal, 2014)
The article considers the consequences of implementation of city models: of an industrial city, a new city, and a scientific center. The complex of elements determined by the idea of life arrangement, projects of spatial organization, milieu of behavior in the realized ‘city samples’ are studied in the article. Special emphasis is laid on users’ (inhabitants’) feeling. Observation of experimental entities is based on the objects that fully represent historical epochs: the industrial period (Leftbank Novosibirsk, 1930s), development of the oil and gas deposits (Novosibirsk, 1960-1980s), building of scientific centers (Novosibirsk Akademgorodok, Krasnoobsk, 1950-1970s). According to the city models, the article considers issues of microdistrict planning, open plans, pedestrian streets, modularity, consequences of mass housing. It pays particular attention to the concept of a big city that denies ideas about closed and monoprofile cities. The investigation carried out in Novosibirsk shows that this concept was conceived in the 1980s. The big city is built on the basis of interaction of different city models. The article pays special attention to the district in Novosibirsk which represents the city’s past.